PERANCANGAN SISTEM INFORMASI PENGOLAHAN DATA PEGAWAI DAN PENGGAJIAN DENGAN METODE WATERFALL (STUDI KASUS PADA PT. INAWAN CHEMTEX SUKSES ABADI) - Merinda Cecilia Wibowo; Prasetyo Adi Nugroho (Institut Teknologi dan Bisnis (ITB) Swadharma, 2021)
PT. Inawan Chemtex Sukses Abadi employee data is important information that is means of recording attendance and payroll processes must be managed appropriately. At this time the procedure applied to employee data processing and payroll at PT. Inawan Chemtex Sukses Abadi still uses conventional methods. This method requires a long time in preparing attendance reports and salary reports. With this, PT. Inawan Chemtex Sukses Abadi is necessary to change the data processing methods of employees and payroll that they use today to become computerized and automated methods. To resolve these problems, the researchers make an information system for employee data processing and payroll. Information systems that are made to be able to make attendance reports and salary reports quickly as accountability to company leaders and the expected results of this study are to produce information systems that can process employee data and payroll that are effective and efficient.